Web-based prototype system for flood simulation and forecasting based on the HEC-HMS model. (December 2022) - Lin, Qiaoying; Lin, Bingqing; Zhang, Dejian; Wu, Jiefeng
Abstract: This study addresses Hydrologic Engineering Center Hydrologic Modeling System (HEC-HMS) model simulation issues in web environments and identifies key model parameters to facilitate practical flood forecasting. Jython scripts serving as an intermedium layer between the web-based forecast system and HEC-HMS model were created to enable HEC-DSS database writing and reading and HEC-HMS model execution as a background process. Empirical relationships between model parameters and time series characteristics were established to mitigate the difficulty in determining event-dependent model parameters. An open-source web-based prototype system for flood simulation and forecasting (WSFF) based on the HEC-HMS was built by incorporating these methods and parameter knowledge into the model and knowledge subsystem. The WSFF performance was evaluated via a case study involving 12 historical flood events in the Chuanchang watershed, southeastern China. Among these 12 events, nine events served as calibration events to establish WSFF parameter knowledge, and three events were used to verify the WSFF performance. A consistent and satisfactory performance in terms of peak flow, total flood volume, peak flow timing and overall hydrograph fitting effect was found. The average Nash–Sutcliffe efficiency (NSE) for the validation events reached 0.81 versus 0.82 for the calibration events. The relative error in peak flow (REP) and relative error in flood volume (REV) indicated a reasonable flood forecasting accuracy, with an REP within 15% and RET within 1 h. Developed as open-source software, the WSFF could serve as a useful basis for the hydrological community regarding HEC-HMS adoption in flood forecasting. Highlights: A wrap-up service was developed to incorporate HEC-HMS into a web-based forecast system. Empirical relationships were established to reduce the difficulty in parameter identification. WSFF was developed by incorporating the wrap-up service and empirical relationships. WSFF was assessed, and overall satisfaction in flood forecasting was observed.